Eksplorasi Jamur Antagonis pada Rhizosfer Asal Tanaman Pala Banda (Myristica fragans HOUTT.) di Kecamatan Leihitu - Novi Wahyuniati; Wihelmina Rumahlewang; Costanza Uruilal (JURNAL PERTANIAN KEPULAUAN, 2023)
Research on the exploration of Antagonic Fungi in the Rhizosphere from the banda nutmeg plant (Myristica fragans Houtt.) in Leihitu district aims to determine the genus of rhizosphere fungi on nutmeg plants that have antagonistic potential against Fusarium sp. and the differences in their antagonistic abilities. Sampling was carried out at 4 locations in Leihitu district, namely, Asululu, Hila, Kaitetu, and Seith, each with 4 plants at each location, thus obtaining 16 rhizosphere soil samples. From 16 samples of the rhizosphere, 17 types of fungi were obtained, and 12 of them were able to become biocontrol, namely Nv-1(62.73%), Nv-3 (63.84%), Nv-4 (61.50%), Nv-5 (64.18%), Nv-7 (60.93%), Nv-8 (60.93%), Nv-9 (63.90%), Nv-10 (61.69%), Nv-12 (61.05%), Nv-13 (63.88%), Nv-16 (60.55%), and Nv-17 (61.23%).